PENGARUH LATIHAN ABC RUNNING TERHADAP POWER TUNGKAI PESERTA DIDIK EKSTRAKURIKULER BOLA VOLI - Wardianto, Wardianto; Simanjuntak, Victor; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is whether Acceleration Balance Coordination (ABC) Running affects the power of leg muscles of students in extracurricular MAN 1 Pontianak. The purpose of this study was to determine the effect of ABC training running on the strength of leg muscle power in jumping smash of extracurricular volleyball game MAN 1 Pontianak The population in this study were 12 people. By taking samples using saturated sample techniques, the number of samples is 12 people. The method used is an experiment with pre-experimental design. Data analysis techniques use the t-test formula. Based on the results of this t-test, obtained t count itung (>) t table, namely the value of t count 1.52 and t table 2.89 with a significant rate of 5%. Then Ho is refused and Ha is accepted. This means that there is an influence on the 12.44% running ABC coordination (ABC) running, on the extracurricular leg muscle power of MAN 1 Pontianak.Keywords: Exercise, ABC running, Power, Volleyball.